Mid‐point transverse process to pleura block for surgical anaesthesia. Issue 1 (11th March 2019) - Costache, I.
Summary: The use of ultrasound in regional anaesthesia has expanded our understanding of regional anaesthesia techniques and allowed for the development of novel strategies to achieve blockade of the trunk. Several alternatives to paravertebral block have recently been proposed, but none of these new techniques have yet been shown to provide surgical anaesthesia equivalent to a paravertebral block. This case report describes the successful use of the mid‐point transverse process to pleura (MTP) block as the sole anaesthetic technique for a patient undergoing breast surgery.